The Effect of Thyme and Cinnamon on the Microbial Balance in Gastro Intestinal Tract on Broiler Chicks - Al-Kassie, Ghalib Alwan Mohamed (International Journal of Poultry Science, 2010)
This study was conducted to determine the effect of the addition of different percent levels of thyme and cinnamon, added to a standard diet, on the gastro intestinal tract. Total bacteria count, coli form bacteria, lactobacilli bacteria and fungal count were determined in different region crop, jejunum and large intestine. Two hundred fifty day-old broilers (Arbor-Acre) were divided into groups of 50 birds each and randomly assigned to the five treatment groups. Each treatment has two replicates. Experiment was as follow. A control group with no thyme and cinnamon and other four groups, with the following additives. 0.5%, 1% thyme and 0.5%, 1% cinnamon. The data showed that the additive thyme and cinnamon has statistical effect (p<0.05) the decrease in the total bacteria count, coli form in group, jejunum and large intestine compared with the control. In conclusion different levels 0.5% and 1% of thyme and 0.5%, 1% of cinnamon used as antimicrobial balance in gastro intestinal tract for broiler chicks.